El marketing estratégico como mecanismo para el posicionamiento del mercado de la fábrica de plumón sintético estratex cantón guano, provincia de chimborazo periodo julio 2016 julio 2017 - Murillo Silva, Elizabeth Fernanda (2018)
The present research deals with Strategic Marketing as a mechanism for the market positioning of the Estratex synthetic down factory Guano canton, Chimborazo province, dedicated to create the synthetic down feedstock for the production of the cardigans, as well as marketing of closures, among others. It is established by four chapters distributed as form. The First Chapter: It described the approach of the problem through the main problem presented by the factory; the justification of how important is the research topic, in order to establish the general objective and specific objectives that allows obtaining the results at the end of the investigation. The Second Chapter: It structured by the art state, presented first by the background of researches conducted previously with the proposed topic, the theoretical framework that is the theoretical, scientific and doctrinal support of the problem treaty where the importance of strategic marketing is treaty, and market positioning. The Third Chapter: It established the research methodology, the type of research and the design that was applied in the execution of the research, as well as the population and sample that it was taken to get necessary information, obtaining the results and interpretation of the research done. The Fourth Chapter: the conclusions were done after the investigation; and the recommendations were established with the purpose of being support for the factory.